The Influence of Multi-Discourse Representation Learning Model on Students’ Mathematical Representation and Communication Skills - Nurma Izzati; Desi Listiyani (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
Students often experience difficulties in representing mathematical concepts and communicating mathematical ideas clearly. This condition indicates that the learning model used needs to be reviewed and developed. This study aims to determine the effect of implementing the Discourse Multi-Representation (DMR) learning model on mathematical representation and mathematical communication abilities. The population was all class XI MA NU Putri Buntet Pesantren Cirebon. The sample was determined using the cluster random sampling method, consisting of two groups, namely the experimental and control classes. This study used a quasi-experimental design with a non-equivalent control group design. The research instrument was a test of mathematical representation and communication abilities arranged in the form of essay questions. The results of the t-test showed that for mathematical representation abilities there was no significant difference between the experimental and control classes. Conversely, for mathematical communication abilities, the use of the DMR model had an effect on students' mathematical communication abilities between the experimental and control classes.